Geographic information systems - GIS, a view from the water resource (2015)
This research paper presents an overview of the state of the art Geographic Information Systems - GIS, which has been defined and characterized important aspects about these systems and their contribution to the analysis of water bodies from various use and development, which allows the achievement of the Platform for water Resources Network of the Colombian Caribbean